Peningkatan Hasil Belajar Siswa pada Materi Adab mengunakan Model Pembelajaran Team Assisted Individualization (TAI) dengan Media Audio Visual di MTsN 1 Kota Lhokseumawe - Rosdiana Rosdiana (Ranah Research : Journal of Multidisciplinary Research and Development, 2023)
The lesson on Aqidah (theology) and Akhlak (morality) aimed to enable students to practice the values they learn in their daily lives. This research aimed to determine how the students’ learning outcomes in Aqidah Akhlak lessons can be improved using the Team Assisted Individualization (TAI) method. The type of this research was classroom action research which was conducted in the eighth grade at MTsN 1 Kota Lhokseumawe, with a population of 210 students and a sample of 30 students from class VIII.1. The Classroom Action Research (CAR) consisted of four phases: planning, implementation, observation, and reflection. The research results showed an improvement in learning outcomes in each cycle. In the pre-cycle phase, out of 30 students, only 7 students (23%) completed the learning objectives, while the remaining 23 students (77%) did not. In the first cycle, there was an improvement as 22 students (73%) achieved mastery of the learning material, while 8 students (23%) did not. In the second cycle, 28 students (93%) completed the learning objectives, while the remaining 2 students (7%) did not.